Permanent Magnet Synchronous Generator Connected to a Grid via a High Speed Sliding Mode Control - Omokhafe James Tola; Edwin A. Umoh; Enesi A. Yahaya; Osinowo E. Olusegun (International Journal of Robotics and Control Systems, 2022)
Wind power generation has recently received a lot of attention in terms of generating electricity, and it has emerged as one of the most important sources of alternative energy. Maximum power generation from a wind energy conversion system (WECS) necessitates accurate estimation of aerodynamic torque and system uncertainties. Regulating the wind energy conversion system (WECS) under varying wind speeds and improving the quality of electrical power delivered to the grid has become a difficult issue in recent years. A permanent magnet synchronous generator (PMSG) is used in the grid-connected wind-turbine system under investigation, followed by back-to-back bidirectional converters. The machine-side converter (MSC) controls the PMSG speed, while the grid-side converter (GSC) controls the DC bus voltage and maintains the unity power factor. The control approach is second-order sliding mode controls, which are used to regulate a nonlinear wind energy conversion system while reducing chattering, which causes mechanical wear when using first-order sliding mode controls. The sliding mode control is created using the modified super-twisting method. Both the power and control components are built and simulated in the same MATLAB/Simulink environment. The study successfully decreased the chattering effect caused by the switching gain owing to the high activity of the control input.